ACUTE METHANOL INTOXICATIONS - A CHALLENGE FOR CLINICAL TOXICOLOGY - Petko Marinov; Snezha Zlateva; Georgi Bonchev; Dobri Ivanov; Marieta Yovcheva; Kaloyan Georgiev (Peytchinski Publishing, 2016)
Purpose: Methanol (CH3OH) is a monohydric alcohol, vastly used both in housekeeping and industry. Although the acute methanol intoxications are rare, they may include life-threatening symptoms, substantial lethality and negative consequences such as neurological disorders and vision damage. Aim of the work is to conduct a retrospective study on the acute methanol intoxications within Varna region for a 10-year period (2006-2015). Material/Methods: This study covers 39 patients of the Clinic for Intensive Treatment of Acute Intoxications and Toxicoallergies at Naval Hospital - Varna, all of which had their diagnosis confirmed, including gas chromatography methods. Results: Methanol intoxication prevalence showed male/female ratio close to 2.9:1. The major part of the cases concerned economically active population, the age group of 25-60 being the most affected. In all instances an oral methanol intake has been involved. Death occurred in 14 cases (35.9%)